Haschek and Rousseaux's handbook of toxicologic pathology. - Haschek, Wanda M.; Rousseaux, Colin George, 1954-; Wallig, Matthew A.; Bolon, Brad (Academic Press, 2023)
Haschek and Rousseaux's Handbook of Toxicologic Pathology, recognized by many as the most authoritative single source of information in the field of toxicologic pathology, has been extensively updated to continue its comprehensive and timely coverage. The fourth edition has been expanded to five separate volumes due to an explosion of information in this field requiring new and updated chapters. Completely revised with a number of new chapters, Volume 2: Toxicologic Pathology in Safety Assessment is an essential part of the most authoritative reference on toxicologic pathology principles and techniques for assessing product safety and human risk. Volume 2 describes the integration of product-induced structural and functional changes in tissues and the interpretation of their biological implications. Completely revised with many new chapters, Volume 2 of the Fourth Edition covers product safety assessment from many angles including current and emerging issues in toxicologic pathology for many product classes. Volume 2 of the Handbook of Toxicologic Pathology is a key resource for pathologists, toxicologists, research scientists, and regulators who use toxicologic pathology methods to study and make decisions on product safety.